In vitro effect of fluoride gels supplemented with nano-sized sodium trimetaphosphate on enamel erosive wear - Nagata, Mariana Emi; Delbem, Alberto Carlos Botazzo [UNESP]; Báez-Quintero, Liliana Carolina [UNESP]; Hosida, Thayse Yumi [UNESP]; Silva, Amanda Monise Dias [UNESP]; Sampaio, Caio [UNESP]; Pessan, Juliano Pelim [UNESP] (Elsevier, 2024)
Objective: To assess the protective effect of fluoride (F) gels supplemented with micrometric or nano-sized sodium trimetaphosphate (TMPmicro and TMPnano, respectively) against enamel erosion in vitro. Methods: Bovine enamel blocks (n = 140) were selected according to their surface hardness, and randomly divided into seven groups (n = 20/group), according to the gels tested: Placebo (without F/TMP), 4,500 μg F/g (4500F), 9,000 μg F/g (9000F), 4500F plus 2.5 % TMPnano (2.5 % Nano), 4500F plus 5 % TMPnano (5 % Nano), 4500F plus 5 % TMPnano (Micro 5 %) and 12,300 μg F/g (Acid gel). Blocks were treated once during one minute with the gels, and submitted to erosive (ERO, n = 10/group) or erosive plus abrasive (ERO+ABR, n = 10/group) challenges 4 times/day, for 90 s for each challenge (under reciprocating agitation), during consecutive 5 days. Blocks were analyzed by profilometry, and by surface (SH) and cross-sectional hardness (∆KHN). Data were submitted to two-way ANOVA, and Fisher's LSD test (p < 0.05). Results: For ERO, both TMPnano-containing gels promoted enamel wear significantly lower than Placebo and 4500F, reaching levels similar to both positive controls (9000F and acid gel); significantly lower softening was observed for enamel treated with 4500F+5 % Micro and 4500F+2.5 % Nano. Also, the lowest ∆KHN values were observed for 4500F+2.5 % TMPnano among the TMP-containing gels. For ERO+ABR, the lowest enamel wear was achieved by the use of 4500F+5 % Nano among all gels, including both positive controls; lower softening was observed for Placebo and 9000F groups. Conclusion: The addition of 5 % nano-sized TMP to a low-fluoride gel produced superior protective effects for enamel under both challenges conditions, when compared with micrometric TMP, reaching values similar to or superior than both positive controls, respectively for ERO and ERO+ABR. Clinical significance: The supplementation of low-F gels with TMP was shown to significantly improve their effects on enamel erosive wear, and the use of nano-sized TMP further enhances this protective action.
Keywords: Dental enamel; Fluorides; Phosphates; Tooth wear